MetroNet: a disruption‐tolerant approach for mobile downloads on metro systems. Issue 8 (30th September 2013) - Tung, Li‐Ping; Chen, Yi‐Chao; Lan, Kun‐chan; Chen, Ling‐Jyh; Mavromoustakis, Constandinos; Shu, Lei; Dagiuklas, Tasos; Xiao, Yang
ABSTRACT In this study, we propose a disruption‐tolerant network based system called MetroNet, which exploits the precise schedules of metro systems to pre‐fetch data and facilitate mobile Internet downloads, even if an end‐to‐end path between the source (i.e. content sources) and the destination (i.e. users) does not exist contemporaneously. Using a comprehensive set of simulations, as well as real‐world scenarios of the Taipei and Atlanta metro systems, we demonstrate that MetroNet can handle the intermittent Internet connectivity caused by mobility and therefore provide a better mobile download service. The simulation results demonstrate that the proposed call admission control algorithm utilises the network resource effectively and provides better quality of service for mobile users than the first‐come‐first‐serve and least‐first algorithms. Copyright © 2013 John Wiley & Sons, Ltd.